2021
DOI: 10.1007/s13311-020-00999-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Level of Exosomal miR-5121 Released from Microglia Suppresses Neurite Outgrowth and Synapse Recovery of Neurons Following Traumatic Brain Injury

Abstract: Activated microglia can suppress neurite outgrowth and synapse recovery in the acute stage following traumatic brain injury (TBI). However, the underlying mechanism has not been clearly elucidated. Exosomes derived from microglia have been reported to play a critical role in microglia-neuron interaction in healthy and pathological brains. Here, we aimed to investigate the role of microglia-derived exosomes in regulating neurite outgrowth and synapse recovery following TBI. In our study, exosomes derived from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Exosomes are small extracellular vesicles, which can be secreted from different cells, including microglia. Microglial exosomes have been implicated in the progression of neurodegeneration [15][16][17][18] and neuronal functioning, including neurite outgrowth [19,20]. Exosomal content has also been shown to change depending on the signals microglia receive [14].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are small extracellular vesicles, which can be secreted from different cells, including microglia. Microglial exosomes have been implicated in the progression of neurodegeneration [15][16][17][18] and neuronal functioning, including neurite outgrowth [19,20]. Exosomal content has also been shown to change depending on the signals microglia receive [14].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this work verified these results in vivo , by infusing exosomes derived from pro-inflammatory microglia, through osmotic mini pumps connected into the hippocampus, showing a decrease by 30% in the spine density ( Prada et al, 2018 ). In a similar way, exosomes derived from BV2 cell culture submitted to stretch injury have reduced levels of miR-5121, which reduces the expression of synaptophysin, postsynaptic density protein 95 (PSD-95), and glutamate receptor 1 (GluR-1), decreasing dendritic spine density ( Zhao et al, 2021 ).…”
Section: Microglia-derived Exosomesmentioning
confidence: 98%
“…The overexpression of miR-5121 in stretch-injured MD-Exos partially reversed the inhibition of neurite outgrowth and neurons’ synaptic recovery by directly targeting RGMa after TBI. Moreover, the motor coordination in miR-5121 overexpressed MD-Exos treated mice was significantly improved after TBI [ 31 ]. One interesting study revealed that MD-Exos-derived miR-124-3p contributes to alleviating neurodegeneration and improving cognitive outcomes after TBI by transferring into neurons and targeting the Rela/ApoE signaling pathway.…”
Section: Cell-derived Exosomes and Exosome-derived Micrornas In Tbimentioning
confidence: 99%